2011
DOI: 10.1245/s10434-011-1627-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Management of Hypothyroidism Following Thyroid Lobectomy: Evaluation of a Clinical Algorithm

Abstract: The incidence of hypothyroidism following TL is low, and a significant proportion of individuals who become biochemically hypothyroid will demonstrate only a transient elevation in their TSH levels. As well, individuals with LI, or GC formation, within their resected thyroid lobe may be at increased risk for post-TL hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 26 publications
5
31
0
Order By: Relevance
“…Routine thyroxine replacement may be recommended, rather than close follow-up monitoring, for some posthemithyroidectomy patients with risk factors, such as elevated thyroid antibody concentrations or histologic evidence of autoimmune thyroiditis (Su et al, 2009). In contrast, other researchers have reported that elevated serum TSH concentration alone may not justify the initiation of thyroid hormone replacement, since nearly 70% of individuals who developed biochemical (asymptomatic) hypothyroidism during the early postoperative period after hemithyroidectomy recovered normal thyroid function without pharmacologic intervention (Johner et al, 2011). Therefore, determination of the true indication is important prior to initiating thyroid hormone replacement therapy.…”
Section: Natural Historymentioning
confidence: 96%
See 4 more Smart Citations
“…Routine thyroxine replacement may be recommended, rather than close follow-up monitoring, for some posthemithyroidectomy patients with risk factors, such as elevated thyroid antibody concentrations or histologic evidence of autoimmune thyroiditis (Su et al, 2009). In contrast, other researchers have reported that elevated serum TSH concentration alone may not justify the initiation of thyroid hormone replacement, since nearly 70% of individuals who developed biochemical (asymptomatic) hypothyroidism during the early postoperative period after hemithyroidectomy recovered normal thyroid function without pharmacologic intervention (Johner et al, 2011). Therefore, determination of the true indication is important prior to initiating thyroid hormone replacement therapy.…”
Section: Natural Historymentioning
confidence: 96%
“…However, hypothyroidism after hemithyroidectomy is an under-reported or underwww.intechopen.com recognized complication, with patients most often monitored only for a short time postoperatively. Recently, however, Johner et al (2011) reported that the overall incidence of early postoperative hypothyroidism was 21.6%, with the incidence of permanent hypothyroidism only 7.8%. In addition to showing that the incidence of hypothyroidism following hemithyroidectomy is low, this study showed that a significant proportion of individuals who become biochemically hypothyroid (asymptomatic) demonstrate only a transient elevation in their TSH levels.…”
Section: Incidencementioning
confidence: 99%
See 3 more Smart Citations